Multiple Renewable Short-Circuit Ratio for Assessing Weak System Strength with Inverter-Based Resources - Lin Yu; Shiyun Xu; Huadong Sun; Bing Zhao; Guanglu Wu; Xiaoxin Zhou (CSEE Journal of Power and Energy Systems)
Inverter-based resources (IBRs), such as wind and photovoltaic generation, are characterized by low capacity and extensive distribution, which can exacerbate the weak properties of power systems. Precise identification of weak system status is essential for ensuring the security and economic efficiency of IBR integration. This paper proposes the index of the multiple renewable short-circuit ratio (MRSCR) and its critical value calculated by the voltage (CMRSCR) to provide a comprehensive assessment of power system strength in the presence of high IBR penetration, enhancing the accuracy and reliability of system strength evaluation. First, we introduce a single-infeed equivalent model of the power system integrating multiple IBRs. We examine the factors associated with system properties that are crucial in the strength assessment process. Subsequently, the MRSCR is derived from this analysis. The MRSCR describes the connection between system strength and voltage variation caused by power fluctuations. This implies that voltage variation caused by IBR power fluctuations is more pronounced under weak grid conditions. Following this, the CMRSCR is proposed to precisely evaluate the stability boundary. The disparity between MRSCR and CMRSCR is utilized to evaluate the stability margin of the power system. Unlike a fixed value, the CMRSCR exhibits higher sensitivity as the system approaches a critical state. These indexes have been implemented in the PSD power tools and power system analysis software package, facilitating engineering calculation and analysis of bulk power systems in China. Finally, simulation results validate the effectiveness of the proposed indexes and the research findings.